INTEGRATED MANAGEMENT OF MAJOR POTATO DISEASES IN GUJARAT - Chaudhari, S. M.; Patel, R. N.; Patel, R. L.; Patel, C. K.; Patel, N. H.; Pandey, S. K. (Potato Journal, 2013)
Potato crop has caught up in many areas of Gujarat state during the last decade due to its proper fitting in the cropping patterns. The major constraint in potato cultivation is quality seed. Seeds procured from different northern states by the potato growers carry many diseases viz., common scab, mosaics. Early blight is an important disease in the major potato growing regions of the state. An integrated approach was adopted for the management of early blight and other tuber borne diseases. The trial was conducted for four years i.e. 1999-2000 to 2002-03 at Deesa in randomized block design with six treatments, five replications and two cultivars viz., Kufri Badshah and Kufri Chandramukhi. The treatment comprising disease free seed of late blight resistant cv. Kufri Badshah + tuber treatment with 3% boric acid for 30 min + optimum date of planting + (two spray of metasystox @ 1 ml/litre of water + one spray of mancozeb 0.2% + rouging + haulm cutting) controlled the diseases like stem necrosis, mosaics and common scab effectively. It has also given maximum tuber yield (391.67 q/ha). Considering the results, it can be inferred that resistant variety against virus diseases is to be grown and tuber treatment with 3% boric acid for 30 minute is to be given prior to sowing for the management of common scab. Two sprays of metasystox @ 1 ml/l of water is to be given for the control of stem necrosis disease with one spray of mancozeb 0.2% to protect the crop against early blight. Timely rouging and haulm cutting is important to prevent the spread of the viral diseases. Such produce can also be used as seed in succeeding years without introduction of tuber born diseases from other areas.